Low level of awareness and prevention of hepatitis B among Congolese healthcare workers: urgent need for policy implementation - Shindano, Tony Akilimali; Horsmans, Yves (Frontiers in Public Health, 2024)
The Democratic Republic of Congo (DRC) is a country with many public health challenges, including those related to the prevention and management of viral hepatitis B. Healthcare workers, who are at the frontline of patient care, are particularly at risk of contracting and spreading this virus, especially given its high prevalence in the general population. This paper examines the level of awareness and preventive measures among Congolese healthcare workers. Overall, the data show that health workers are under-immunized and lack formal training in hepatitis B prevention and management. In addition to limited awareness, health facilities are insufficiently involved in the implementation of standardized infection control protocols, the provision of personal protective equipment and routine hepatitis B vaccination programmes. There also appears to be a lack of clear and effective national policies outlining the main axes of infection control targets by 2030. This calls for urgent policy implementation focusing on mandatory vaccination, training, resource availability, adherence to infection control practices and comprehensive post-exposure management.